KERJASAMA ORANG TUA DENGAN GURU DALAM MENINGKATKAN AKTIVITAS BELAJAR SISWA MTS NURUL ASRAR PANGGUNG PAKAMBAN DAYA SUMENEP - M Sahibudin (Universitas Islam Madura, 2019)
As stated by Kartono et al., One of the main obligations and rights of parents who cannot be separated is educating children, because parents give life to children and they have a very important obligation to educate their children, besides that, the school also holds important role for the implementation of education. Thus, collaboration between parents and teachers is important so that the implementation of educational activities can run smoothly. Therefore researchers are interested in the research. And from the results of the research carried out it can be described as follows: 1) that parent and teacher cooperation on the success of students in school is absolutely necessary, 2) It is very necessary to have parents and teacher cooperation to support and improve learning activities for educational success, 3 ) The parent and teacher approach has a considerable influence on the success of student learning, both at school and at home, 4) The results of the study show that MTs Nurul Asrar Panggung students, with the cooperation of parents and good teachers, are quite influential for children's learning activities at school.